Hechos y Tachas: value, facts, and bodies in the early modern Caribbean - Pablo F. Gómez (Tapuya)
This article examines the emergence of ideas about corporeal hechos [facts] in the sixteenth- and seventeenth-century Caribbean. The establishment of facts around the human flesh in the early modern Caribbean and their circulation occurred in multiple social and cultural spaces but was prominent in the world of slave trading. This development depended on the creation of categories for the fixation of the flesh in the public discourse that appeared in governmental, judicial, and private records in locales in Europe and the Americas. At the same time, the development of this Caribbean tradition of facts required the circulation of these ideas and categories as inscribed in procedures of tacit knowledge related to bodies, practices that were evident in the work of slave-trading communities in the region. The creation of bodily facts emerged, in the end, from techniques that inscribed human bodies in accounts and transactions of all sorts moving across the Atlantic.